Personal Hygene Dengan Kejadian Dermatitis Di Desa Haria Kecamatan Saparua Maluku Tengah Tahun 2021 - Windatania Mayasari; Dewi Susanti (Pusat Riset dan Inovasi Nasional, 2023)
Dermatitis is inflammation of the skin (epidermis and dermis) as a responder to the influence of oxygen factors and / or endpgen factors, causing clinical abnormalities in the form of inflorescences, polymorphics and itchy complaints. Personal hygiene is a rare or act of maintaining personal hygiene and physical and mental health, personal protective equipment is an effort to prevent dermatitis, because using personal protective equipment can avoid direct contact with chemicals. This study is to determine the relationship between personal hygiene and the use of personal protective equipment with the incidence of dermatitis in traditional fishermen in Haria Village, Saparua District, Central Maluku Regency. This research is a type of quantitative research with an approach using a sectional cros design. The sampling technique used is using the total sampling technique, which is a sampling technique when members of all populations are used as samples, the measuring instrument used is a questionnaire. Data analysis using univariate and bivariate analysis using chi-square test. This study showed a relationship between personal hygiene with the incidence of dermatitis (p-value = 0.04) and the use of personal protective equipment with the incidence of dermatitis (p-value = 0.03). The conclusion is that there is a relationship between pesonal hygiene, the use of personal protective equipment with the incidence of dermatitis, fishermen's advice to pay more attention to personal hygiene and use protective equipment.